Counsellor Ideal Character Based on Javanese Cultural Values - Habsy, Bakhrudin All; Mariani Binti Md Nor (ILIN Education Indonesia, 2024)
When dealing with other people, especially counsellors, counsellors must be able to be ngemong by showing a tolerant attitude, not reproaching, not demanding and helping them in fulfilling their needs. by showing a ngemong attitude, the counsellor will show himself as a trustworthy and compassionate person. Of course, professional counsellors have at least reached the level of